2012
DOI: 10.1371/journal.pone.0048704
|View full text |Cite
|
Sign up to set email alerts
|

MYC Gene Delivery to Adult Mouse Utricles Stimulates Proliferation of Postmitotic Supporting Cells In Vitro

Abstract: The inner ears of adult humans and other mammals possess a limited capacity for regenerating sensory hair cells, which can lead to permanent auditory and vestibular deficits. During development and regeneration, undifferentiated supporting cells within inner ear sensory epithelia can self-renew and give rise to new hair cells; however, these otic progenitors become depleted postnatally. Therefore, reprogramming differentiated supporting cells into otic progenitors is a potential strategy for restoring regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 94 publications
3
22
0
Order By: Relevance
“…Further, the findings of adult SCs with intense, pan-nuclear γH2AX that were positive for cleaved caspase-3 and showed only negligible Rad51 expression suggested that incomplete DNA repair could lead to apoptosis. These results are consistent with prior data showing signs of apoptosis of cell cycle reactivated SCs of the adult utricle upon c-Myc overexpression [38]. What might be the mechanisms underlying slower kinetics of DNA damage signaling in adult SCs?…”
Section: Discussionsupporting
confidence: 93%
“…Further, the findings of adult SCs with intense, pan-nuclear γH2AX that were positive for cleaved caspase-3 and showed only negligible Rad51 expression suggested that incomplete DNA repair could lead to apoptosis. These results are consistent with prior data showing signs of apoptosis of cell cycle reactivated SCs of the adult utricle upon c-Myc overexpression [38]. What might be the mechanisms underlying slower kinetics of DNA damage signaling in adult SCs?…”
Section: Discussionsupporting
confidence: 93%
“…This indicated that overexpression of Pax2 could stimulate the proliferation of supporting cells but was not enough to regenerate cochlear hair cells. Similarly, another study37 reported that co-infection of utricles with adenoviral vectors encoding the degradation-resistant T58A mutant of c-Myc (c-MycT58A) triggered significant levels of supporting cell S-phase entry in adult vestibular sensory epithelium, but only a small number of the proliferating cells differentiated into hair cells. These results suggest that inducing hair cell differentiation in addition to promoting residual supporting cell proliferation is necessary for hair cell regeneration.…”
Section: Discussionmentioning
confidence: 90%
“…CyclinD1 expression declines as hair cells and supporting cells exit the cell cycle, and forced expression of cyclin D1 in neonatal and adult mouse utricles triggers cell cycle reentry of hair cells and/or supporting cells [177, 178]. Conditional deletion of N-Myc in the embryonic ear reduces growth of the sensory epithelium by inhibiting proliferation [179, 180], and overexpression of N-Myc (J. Burns, unpublished results) or c-Myc, a closely related family member, results in robust proliferation of supporting cells in the adult mouse utricle in vitro [181]. Neither cyclin D1 nor c-Myc overexpression is able to induce re-growth of the sensory epithelium, as proliferating cells either become arrested in G2 or undergo apoptosis after passing through M phase, apparently due to accumulation of DNA damage [182].…”
Section: Lessons From Development: Molecular Level Control Of Prolmentioning
confidence: 99%